What influences parents’ decisions to use sustainable mode (public bus) with their children? A case study in Batu Pahat, Johor - Mohd Yahya, N A S; Ahmad Termida, N; Daniel, B D; Othman, M H (2023)
Malaysia is facing a challenge on how to improve the quality of public transportation system along with the city’s urbanization since public transport is one of the sustainable approaches to minimise the use of private vehicles on road that mainly contributes to CO2 emissions that affect the environment, negatively. The lack of public transport services has become a barrier for people to access all the facilities and socialize among the community. Studies on the use of public transport by children are rarely discussed and has lack of attention among community. Thus, this study aims to determine parents’ perceptions in using sustainable mode such as public bus with children in terms of accessibility, affordability, safety and comfortability, as well as to analyse the subjective factors affecting parents’ decisions to use public bus with their children based on the Theory of Planned Behaviour (TPB). The survey method via questionnaire has been distributed through face-to-face (self-administered questionnaire) and online method (via Google Form) among 100 adults (aged 18 and above, and married) who lives in Batu Pahat, Johor. Then, the data were analyzed by applying Mean Score Method and multiple linear regression analysis using Microsoft Excel. The results show that safety is the main aspect influencing parents' decisions to use public buses with their children. In addition, Attitudes and Perceived Behavioural Control are found to be the significant components influencing Intention, and the Intention influences parents' decisions to use public bus with children for all activity types